Analysis of protease activity of melinjo (Gnetum gnemon L.) skin on the tenderness of buffalo meat - FAISAL ABDURRAHMAN; OTHMAN OMAR; ISWADI ISWADI (Jurnal Natural, 2023)
To enhance the tenderness of meat, it can be accomplished physically or chemically. In chemical way, the process can be accomplished using protease enzymes that can be obtained from fruit, the higher the protease enzyme activity, the softer the meat. In this experiment, the extract and juice of melinjo skin (Gnetum gnemon L) was used to examine the protease enzyme activity. Papaya (Carica papaya) and pineapple (Ananas comosus) were used as a comparison. The research was conducted to understand the influence of incubation time (t) and incubation temperature (To) towards the optimum activity characteristic of protease enzyme on the juice and the extract of melinjo skin, papaya and pineapple. The incubation time of juice and extract was from 0 to 90 minutes with incubation temperature of 37 C and incubation time at 20 minutes with incubation temperature range from 20 to 80C. The protease enzyme activity of juice and extract expand significantly (p0.05) in conjunction with the increase of incubation time and temperature. The research results revealed that the maximum activity of protease enzyme detected at incubation time of 90 minutes for melinjo juice and pineapple skin, and 10 minutes for papaya. The optimum incubation temperature of melinjo skin at 70 C, papaya at 60C and pineapple juice at 60C. Meanwhile, the maximum activity of protease enzyme from melinjo extract identified in the incubation time at 80 minutes, papaya at 90 minutes and pineapple 60 minutes, whereas the incubation temperature of melinjo skin juice at 60 C, papaya at 80  C and pineapple at 30C.